Wave activity at ionospheric heights above the Andes Mountains detected from FORMOSAT-3/COSMIC GPS radio occultation data - de la Torre, Alejandro (2014)
An estimation of the ionospheric wave activity, derived from 4 years of FORMOSAT-3/ COSMIC GPS (Taiwan's Formosa Satellite Mission 3/Constellation Observing System for Meteorology—Global Positioning System) radio occultation electron density data, is presented. A systematic enhancement at the eastern side of the Andes range with respect to the western side is observed. A fitting method to remove the wavelike component from each measured profile and estimate the wave activity is described. The differential effect introduced by the action of orography on the generation, to the eastern side of the Andes, of mountain waves, deep convection waves, or even secondary waves aloft after momentum deposition in the middle atmosphere, is suggested.